1986
DOI: 10.3382/ps.0652318
|View full text |Cite
|
Sign up to set email alerts
|

Involution of Bursa of Fabricius in Male and Female Chickens: A Light Microscopic Histoquantitative Study

Abstract: A histoquantitative study of the bursa of Fabricius in 3- and 6-month-old male Prelux Bro chickens (domestic selection) was made. All compartments of normal bursal tissue were examined. At 3 months of age, there were no significant differences in bursal weight and structure between males and females. The only difference observed was the higher volume density of follicular cortex and the lower proportion of follicular medulla in males compared to females. In 6-month-old male and female chickens, a different deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The regression of the bursa of Fabricius in chukar partridge (Alectoris chukar) and ring-necked pheasant (Phasianus colchicus) is accomplished by a decrease in the bursal weight, which is more prominent in the male than in the female, and the same was observed in the domestic selection of Prelux Bro chickens (Milicevic et al, 1986). Nevertheless, and in contrast with the above data, Mercer-Oltjen and Woodard (1987) observed that in the ring-necked pheasants (Phasianus colchicus), the decline was parallel in both sexes.…”
Section: Bursa Of Fabriciusmentioning
confidence: 68%
“…The regression of the bursa of Fabricius in chukar partridge (Alectoris chukar) and ring-necked pheasant (Phasianus colchicus) is accomplished by a decrease in the bursal weight, which is more prominent in the male than in the female, and the same was observed in the domestic selection of Prelux Bro chickens (Milicevic et al, 1986). Nevertheless, and in contrast with the above data, Mercer-Oltjen and Woodard (1987) observed that in the ring-necked pheasants (Phasianus colchicus), the decline was parallel in both sexes.…”
Section: Bursa Of Fabriciusmentioning
confidence: 68%
“…These top enriched transcription factors in the H3K27ac DERs between non-treated Fayoumi and Leghorn suggest potential differences in binding activity between the lines, which implicate that B-cell development may vary between the lines. This is unsurprising given that bursal development can differ between lines (MiliĆEviĆ et al, 1986). Further studies collecting phenotypic data such as immune cell profiles and populations using flow cytometry across lymphoid tissues of the two lines are warranted to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…At the age of 5 months in chickens and 4 months in pigeons, bursal atrophy can be noticed (Naukkarinen & Sorvari, 1984;Bickford et al, 1985;Sanchez-Refusta et al, 1996). Bursal involution is faster in male chickens than in hens (Milićević et al, 1986). When involution is complete, at the age of 6 months, only a fibrotic residue without intact lymphoid structures remains (Naukkarinen & Sorvari, 1984;Bickford et al, 1985).…”
Section: Introductionmentioning
confidence: 87%